317. ABSOLUTE LYMPH NODE YIELD AND LYMPH NODE RATIO ARE PREDICTORS OF SURVIVAL AND IMPORTANT QUALITY METRICS IN ESOPHAGEAL CANCER SURGERY. (24th September 2022) - Bolger, Jarlath; Tavakoli, Iran; Espin-Garcia, Osvaldo; Castro, Pedro Perez; Marwah, Anindita; Darling, Gail; Yeung, Jonathan
Abstract: Surgical resection following neoadjuvant therapy remains the cornerstone of curative management of esophageal cancer. In spite of this, there remains uncertainty regarding the optimal radicality of lymphadenectomy, and whether increasing lymph node yields confer a true survival benefit. This study aims to assess the impact of lymph node (LN) yield and LN ratio on survival following surgery for esophageal cancer, in addition to identifying factors that may influence LN yield and radicality of resection. All patients undergoing esophagectomy with curative intent from January 1, 2010 to December 31, 2020 were reviewed. Clinical and pathological variables were assessed, with univariable, multivariable, regression and survival analyses performed as appropriate. Cutpoint analysis was used to determine the optimal lymph node ratio. 397 patients underwent esophagectomy, with 288 having a minimally invasive operation (MIE). Stage (stage 3 HR: 1.64 (1.02–2.62), p = 0.04, stage 4 HR: 2.50 (1.43–5.01), p = 0.001), margin status (HR: 2.62 (1.57–4.36), p < 0.001), LN yield <15 (HR: 2.62 (1.57–4.36), p < 0.001) and elevated LN ratio (HR: 8.42 (2.85–24.90, p < 0.001) predicted survival. Patients undergoing MIE had higher LN yields compared with open (30.7 vs 25.3, p < 0.001). Patients undergoing neoadjuvant chemoradiation had lower LN yields compared with those without neoadjuvant therapy and those with neoadjuvant chemotherapy (26.4 vs 30.6 vs 36.8 respectively, p < 0.001). LN ratio < 0.05 was associated with a survival benefit. Lymphadenectomy is a cornerstone of resection of esophageal cancer. Low LN yield and high LN ratio are associated with reduced overall survival. Maintaining a LN yield >15 should remain a key quality metric. A LN ratio of <0.05 is associated with a significant survival benefit.